PENINGKATAN HASIL BELAJAR IPS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE KANCING GEMERINCING DI SD - Asteriyana, Endang (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The purpose of this study is the objective of this study is the increase in the Student Learning Outcomes Learning IPS using Cooperative Learning Model type rattling. Learning Outcomes meeting first cycle I with an average of 65.86 and a second the first cycle with an average of 76.33, while the end of the second cycle test student increased to 82.43. From the results of tests carried out  level of students' understanding of the material increases. Kata Kunci: peningkatan, pembelajaran, model, kooperatif